Direct and residual contact toxicity of insecticides to Halyomorpha halys (Hemiptera: Pentatomidae). Issue 2 (24th January 2019) - Gradish, A.E.; Fraser, H.; Scott-Dupree, C.D.
Abstract: Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) is a serious invasive pest of many agricultural and horticultural crops in Canada and the United States of America. To mitigate economic loss for growers, effective management options for H. halys are needed. We evaluated the efficacy of 12 insecticides ( Beauveria bassiana (Balsamo-Crivelli) Vuillemin (Cordycipitaceae), boric acid, chlorpyrifos, clothianidin, flupryadifurone, λ-cyhalothrin, malathion, novaluron, sulfoxaflor, thiamethoxam, thiamethoxam + λ-cyhalothrin, and thiamethoxam + novaluron) currently used or with potential for H. halys management by determining their direct and residual contact toxicity to H. halys nymphs. Each insecticide was tested at its Canadian label rate and half and twice that rate. With the exception of chlorpyrifos, nymph mortality was low (< 40%) following direct or residual contact exposure to all insecticides and rates. All surviving nymphs were severely affected ( i.e., knocked down) by direct and residual contact exposure to neonicotinoids, while approximately 66% of nymphs were severely affected following exposure to sulfloxaflor residues at label and twice label rate. However, few nymphs were severely affected by all other insecticides and rates. Overall, our results suggest that H. halys is not susceptible to many insecticides at current label rates for Canada. More research is needed to identify efficacious insecticides for H. halys .